2002
DOI: 10.1051/lait:2002023
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: -NIZO food research (The Netherlands) has been working for the food industry, the dairy industry in particular, for over 50 years. During the past 15 years NIZO food research has put a lot of effort into developing predictive computer models for the food industry. Nowadays the main challenges in the production of powders are the development of specialities (having a high added value) and the reduction of processing costs. For this, the production capacity of available installations is maximised and the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Computational fluid dynamics (CFD) allow study of the consequences of modifications in operating conditions (temperature, flow rate) and process configuration with regard to particle characteristics (temperature, water content) and trajectories in the dryer (Ducept et al, 2002;Verdurmen et al, 2002). Nevertheless a numerical simulation of a real evaporator process is not accessible in practice: complex geometry (evaporation tubes, pipelines, pumps, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) allow study of the consequences of modifications in operating conditions (temperature, flow rate) and process configuration with regard to particle characteristics (temperature, water content) and trajectories in the dryer (Ducept et al, 2002;Verdurmen et al, 2002). Nevertheless a numerical simulation of a real evaporator process is not accessible in practice: complex geometry (evaporation tubes, pipelines, pumps, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated control over size, shape and structure of nanostructured metal oxides to achieve unique properties for LIBs [7]. Structures such as nanofibers [8], mesoporous particles threaded with carbon nanotubes [9], hollow octahedra [10], nanowires [11], pillow-shaped porous structure [12], zero-dimensional nanoparticles [13], one dimensional nanowires [14][15][16], nanorods [17][18], nanotubes [18][19], nanoneedles [20], and nanoflakes [21] have been investigated. The preparation of these materials however typically relies on complicated methods with multi-step procedures which limit commercial scalability [19][20]22].…”
mentioning
confidence: 99%